Inovasi Sistem Bioflok Dengan Sumber Bakteri Berbeda Untuk Budidaya Berkelanjutan Benih Kakap Putih (Lates calcalifer) - Rahayu, Dini; Jamal, Endang; Pattinasarany, Agapery Y. (University of Pattimura, 2024)
Biofloc is one of the advances in fish farming technology with the main principle of recycling nutrients into the culture system. Biofloc application has been widely used in freshwater aquaculture systems, but in seawater aquaculture systems it is still very limited. This study evaluated the application of bioflocs with different bacterial sources, EM4_Fishery and Nitrobac, on the growth and survival of White Snapper (Lates calcalifer) and the water quality of the aquaculture environment. This study used a completely randomised design (CRD) with three replications. A total of 19 White Snapper fish with an average weight of 6.86±0.17 g/L were put into each 14-day-old biofloc and control. Feeding was 2% of total body weight with a frequency of once a day (09.00 am). The results showed that during the experimental period, the weight of White Snapper fish decreased variably in both treatments and controls. The survival rate of White Snapper fish in the Nitrobac bacteria treatment tended to be higher than in the EM4_Fishery bacteria, but both were lower than the control with a tendency for large fish to survive longer than small fish. Concentrations of ammonia, nitrite and nitrate in the treatments at the beginning of the experiment were higher than the control but tended to decrease with the length of rearing. DO values tended to increase in the treatments compared to the control, while DO values tended to increase in the treatments compared to the control. These findings revealed that the Nitrobac as a source of biofloc bacteria in marine White Snapper culture is more effective than EM4_Fisheries, but requiring further experiments with some concern on individual fish size greater than 7 g and the biofloc older than two weeks is recommended.